Indonesian Vocational Education Workplace Development - Ismara, Ketut Ima; Setiadi, Bayu Rahmat; Widodo,; Kuncoro, Idris Hadi (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is now facing Industrial Revolution 4.0. It demands vocational education to be more adaptable in responding the changing model of learning which uses digital equipment in the classroom. Classrooms need to be equipped with supporting facilities such as computers as a control center for all learning resources in the classroom (Interactive Instruction Center, Resource & Class Management Server, Interactive Classroom Server), interconnected multimedia equipment and a strong internet network. Moreover, class characteristics that support the learning of the Industrial Revolution Era 4.0 accommodate the improvement of 4C’s skills, i.e. critical thinking, creativity, communication, and collaboration. Therefore, the classroom layout, furniture and room size is easily changed, class is easy to be transformed into spaces with functions different (discussion room, consultation room, independent study, research, etc.). The integration of computer equipment, internet and multimedia in the classroom is needed to realize the learning system in the Indonesian Revolution 4.0 era. Each class room must have an HVAC (heating, ventilation, and air conditioning) system that is able to provide students with a comfortable learning process. Classrooms must be equipped with low-level electrical plugs spread evenly across the walls of the room, smooth and flat floors to facilitate furniture rearrangement, lighting that can be adjusted for group discussions, presentations, and video recording.